(untitled) (Contemporary Journal of Social Science Review, 2026)
Artificial Intelligence (AI) increasingly reshapes higher education institutions by influencing governance systems, teaching models, research processes, and administrative operations. Institutional readiness for AI requires digital infrastructure, policy frameworks, staff competencies, ethical safeguards, and innovation-supportive culture. Leadership plays a central role in enabling such transformation, yet empirical evidence from developing regions remains limited. This study examined the role of transformational leadership in building AI-ready universities in Khyber Pakhtunkhwa (KP), Pakistan. A quantitative cross-sectional survey was conducted with 37 academic heads and institutional representatives from major KP universities. Transformational leadership (12 items) and AI readiness (23 items) were measured using Likert-scale instruments. Reliability analysis showed acceptable internal consistency (α = .657 for leadership; α = .612 for AI readiness). Correlation analysis revealed a moderate positive relationship (r = .488, p < .01). Regression analysis indicated that transformational leadership significantly predicted AI readiness (β = .377, p = .002). The findings demonstrated that leadership behaviors such as vision communication, intellectual stimulation, and staff support significantly aligned with institutional AI preparedness. The study contributed empirical evidence from KP and highlighted leadership development as a strategic lever for AI-driven university transformation.